Anti-Foc RT4 Activity of a Newly Isolated Streptomyces sp. 5–10 From a Medicinal Plant (Curculigo capitulata) - Yun, Tianyan; Zhang, Miaoyi; Zhou, Dengbo; Jing, Tao; Zang, Xiaoping; Qi, Dengfeng; Chen, Yufeng; Li, Kai; Zhao, Yankun; Tang, Wen; Huang, Jiaquan; Wang, Wei; et al. (Frontiers in Microbiology, 2021)
Fusarium wilt of banana caused by Fusarium oxysporum f. sp. cubense (Foc) is a disastrous soil-borne fungal disease. Foc tropical race 4 (Foc TR4) can infect almost all banana cultivars. Until now, there is a shortage of safety and effective control methods and commercial banana cultivars with a resistance against Foc TR4. Biocontrol using environmentally friendly microbes is a promising strategy for the management of Foc TR4. Here, a strain 5–10, newly isolated from a medicinal plant (Curculigo capitulata), exhibited a high antifungal activity against Foc TR4. Combing the morphological characteristics and molecular identification, strain 5–10 was classified as a Streptomyces genus. The sequenced genome revealed that more than 39 gene clusters were involved in the biosynthesis of secondary metabolites. Some multidrug resistance gene clusters were also identified such as mdtD, vatB, and vgaE. To improve the anti-Foc TR4 activity of the strain 5–10 extracts, an optimization method of fermentation broth was established. Antifungal activity increased by 72.13% under the fermentation system containing 2.86 g/L of NaCl and 11.57% of inoculation amount. After being treated with the strain 5–10 extracts, the Foc TR4 hyphae shrinked, deformed, and ruptured. The membrane integrity and cell ultrastructure incurred irreversible damage. Streptomyces sp. 5–10 extracts play a fungicidal role in Foc TR4. Hence, Streptomyces sp. 5–10 will be a potential biocontrol agent to manage fungal diseases by exploring the microbial fertilizer.